The domestic dimension of sports diplomacy - Kobierecki, Michał Marcin (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Sports diplomacy is a tool of foreign policy. Similarly to public diplomacy, for which sports diplomacy is a sub-category, it may also have a domestic dimension. The objective of the research was to overview key types of sports diplomacy activities pursued by governments from the perspective of their internal political significance and to answer the research question whether sports diplomacy may be used to influence the domestic public.
Keywords: sport; politics; sports diplomacy; public diplomacy; domestic politics